Pengelolaan Dunia Pendidikan di Indonesia; Tinjauan Kritis terhadap Sumberdaya Manusia dan Kebijakan, Perspektif Konvensional dan Perspektif Islam - Hotimah, Husnul; Rohman, Baeti (Fakultas Tarbiyah dan Ilmu Tarbiyah, Universitas PTIQ Jakarta, 2022)
Education plays an important role in the development of a country, Indonesia is no exception. Good education management will give birth to superior human resources born from the education space, on the other hand, poor education management cannot be a driving force for the progress of the nation. In the context of Indonesia, there is still a lot of homework in the world of education that needs to be addressed seriously, for example in the aspect of government policy on education and the quality of teaching staff, another problem is the inequality of educational infrastructure, especially in remote areas. It is very important to take collective steps to solve problems in the world of education. At the elite level, it takes the government's intention and awareness to realize policies that favor the world of education, especially regarding the amount of the budget for the education sector, the education budget should still need to be increased if you want to achieve quality education. Islam pays special attention to education, there are many verses in the Qur'an that explain education, even specifically Islam views noble people who have knowledge by elevating their degrees.